2015
DOI: 10.1021/acs.jpcc.5b01943
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Oxidation States on Pyrite Surface Sites

Abstract: Density functional calculations have been performed to study the interaction of oxygen with clean and defective pyrite (100) surfaces. Molecular adsorption states are predicted to undergo dissociation because atomic chemisorption is far more favorable thermodynamically for all surfaces. On the defect-free FeS2 surface molecular adsorption takes place on neighboring iron sites in a side-on fashion. S-adatoms react weakly with O2 whereas S-vacancies bind very strongly molecular oxygen. Dissociative chemisorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…This suggests that the surface O atoms can modify the local electronic structure and optical band gap of the surface. 41,42 Under photoirradiation, the domain products are preferred over olefins on oxygen-decorated Fe 5 C 2 (111), whereas for pure Fe 5 C 2 (111), the formation of alkane is more favorable. We believe that (1) the presence of Fe 5 C 2 in the oxygen-decorated catalyst is responsible for the light-heat transformation and (2) the existence of a small amount of FeO x species on Fe 5 C 2 as a heterostructure also absorbed light, was stimulated, and interacted with the reactants, resulting in a different reaction path and different product distribution.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the surface O atoms can modify the local electronic structure and optical band gap of the surface. 41,42 Under photoirradiation, the domain products are preferred over olefins on oxygen-decorated Fe 5 C 2 (111), whereas for pure Fe 5 C 2 (111), the formation of alkane is more favorable. We believe that (1) the presence of Fe 5 C 2 in the oxygen-decorated catalyst is responsible for the light-heat transformation and (2) the existence of a small amount of FeO x species on Fe 5 C 2 as a heterostructure also absorbed light, was stimulated, and interacted with the reactants, resulting in a different reaction path and different product distribution.…”
Section: Resultsmentioning
confidence: 99%
“…At the (101) ) species. A number of earlier ab initio calculations have also identified the formation of a superoxo and peroxo species via electron transfer from iron sulfide mackinawite 39 and pyrite [57][58][59] surfaces. For water adsorption, whereas less charge is transferred from the (001), (101) and (110) surfaces to the molecular water species, a significant amount of charge is drawn by the dissociated species.…”
Section: Charge Transfers and Oxidation Mechanism Of Zn 3 P 2 Surfacesmentioning
confidence: 99%
“…In realistic mineral systems, the existence of surface imperfections (e.g., vacancies, impurities, etc.) is inevitable. The presence of any imperfection alters the interactions between adsorbents and adsorbates. , Using a semiempirical quantum-chemical approach, Simpson et al revealed that the degree of wettability of the sphalerite surface depends critically on the impurity levels. Correspondingly, doping the ZnS surface with Cu and Fe atoms altered the hydrophobic nature of the surface with the order of Cu-doped > undoped > Fe-doped ZnS surface.…”
Section: Introductionmentioning
confidence: 99%
“…Correspond-ingly, doping the ZnS surface with Cu and Fe atoms altered the hydrophobic nature of the surface with the order of Cu-doped > undoped > Fe-doped ZnS surface. In another study, Rozgonyiet and Stirling 42 simulated the oxidation behavior of defect-free and sulfur-deficient pyrite surfaces by DFT. The results showed that for the S-deficient slab, the O 2 molecule prefers to adsorb on the S-vacant site, either in the molecular or dissociative manner.…”
Section: Introductionmentioning
confidence: 99%